Surface-enhanced Raman scattering of glyphosate on dispersed silver nanoparticles: A reinterpretation based on model molecules - Feis, Alessandro; Gellini, Cristina; Ricci, Marilena; Tognaccini, Lorenzo; Becucci, Maurizio; Smulevich, Giulietta (Vibrational spectroscopy, 2020)
Glyphosate is a wide spread organophosphate herbicide whose use and associated risks are strongly debated. Many countries are regulating its use in field and it is often found in surface water. Therefore, a simple analytical method, possibly based on portable instruments, would be highly desirable. In case of many other pesticides, surface enhanced Raman scattering (SERS) spectroscopy was shown to be a very effective method to approach the problem. Glyphosate Raman and SERS spectra have been subject of different experimental and theoretical studies but still their interpretation is unclear and sensitivity in SERS experiments is quite low. In this work, SERS spectra on silver nanoparticles dispersion of glyphosate, its 2-13C isotopically substituted derivative, and its degradation product, the aminomethylphosphonic acid, have been obtained. The vibrational spectra of this latter compound allowed us to rule out a possible contribution of this species to the SERS spectra and the observed isotope shifts help to explain the SERS pattern in terms of the orientation of the adsorbed molecules on the metal surface. Therefore, we conclude that the relevant differences both on the intensities and wavenumbers between our SERS and Raman spectra of glyphosate must derive from the effect induced by the adsorption on the nanoparticles.